O processo de inclusão escolar no municipio de Ibiúna: descobrindo caminhos...rompendo com equívocos - Gavioli, Maria Aparecida Ouvinhas (2006)
The starting point of study is the question: How to evolve from integration to inclusion? How can regular and special schools overcome errors and assume new roles?" It was conceived at Municipal Special Education School Novo Arco-Íris , in Ibiúna, and was enriched by the experience of many teachers, students, parents, and principals, united by a desire for a better education for everyone. Therefore, this is a collective study, shared by many authors and people, whose lives fortunately have crossed with this project, which seeks to understand the proposed process of School Inclusion of the City of Ibiúna, including its theoretical and practical premises. This investigation involved qualitative fieldwork, originally of an exploratory nature, which evolved to an analysis of some selected schools. The analyses and interpretations used methodological approaches based on new educational paradigms and the concept of a single school, open to everyone. The recommendations of this research indicate that effective school inclusion requires more than the school s commitment, that is, more comprehensive public policies to ensure improved living conditions for the population. They also suggest some education issues that require urgent action, with prospects for change.